Willingness and uptake of the COVID-19 testing and vaccination in urban China during the low-risk period: a cross-sectional study - Suhang Song; Shujie Zang; Liubing Gong; Cuilin Xu; Leesa Lin; Mark R. Francis; Zhiyuan Hou (BMC, 2022)
Abstract Background Regular testing and vaccination are effective measures to mitigate the ongoing COVID-19 pandemic. Evidence on the willingness and uptake of the COVID-19 testing is scarce, and the willingness and uptake of vaccination may change as the pandemic evolves. This study aims to examine willingness and uptake of COVID-19 testing and vaccination during a low-risk period of the COVID-19 pandemic in urban China. Methods A cross-sectional online survey was conducted among 2244 adults in urban China. Descriptive analyses were performed to compare the respondents' willingness and uptake of COVID-19 testing and vaccination. Multivariate logistic regressions were fitted to investigate factors associated with the willingness and uptake of the two measures. Results In early 2021, about half (52.45%) of the respondents had received or scheduled a COVID-19 test at least once, and a majority (95.63%) of the respondents were willing to receive testing. About two-thirds (63.28%) of the respondents had received/scheduled or were willing to receive a COVID-19 vaccine. Willingness and uptake of COVID-19 testing were not associated with socio-demographic characteristics, except for occupation. Being of older age, migrants, having higher educational attainment and secure employment were associated with a higher uptake of COVID-19 vaccination among the surveyed respondents, while willingness to vaccinate was consistent across socio-demographic characteristics among those who had not been vaccinated. Conclusions By early 2021, Chinese adults expressed almost universal willingness of COVID-19 testing and over half of adults have been tested, while the willingness and uptake of COVID-19 vaccination were relatively low at the low-risk period of the COVID-19 pandemic. Maintaining willingness of COVID-19 vaccination is critical and necessary, especially when the pandemic evolved into a low-risk period.